Author Correction: Phosphocode-dependent functional dichotomy of a common co-receptor in plant signalling. (29th November 2018) - Perraki, Artemis; DeFalco, Thomas; Derbyshire, Paul; Avila, Julian; Séré, David; Sklenar, Jan; Qi, Xingyun; Stransfeld, Lena; Schwessinger, Benjamin; Kadota, Yasuhiro; Macho, Alberto; Jiang, Shushu; et al.
In Extended Data Fig. 5d of this Letter, the blots for anti-pS612 and anti-BAK1 were inadvertently duplicated. This figure has been corrected online.